Rancang Bangun dan Pengujian Anemometer Untuk Sudu Savonius - Kaprawi Sahim; Sawalluddin Sawalluddin (Jurnal Rekayasa Mesin, 2020)
In obtaining wind speed data, it is needed a tool that is able to capture the speed of the wind that is converted to the rotation of the shaft. The tool is called an anemometer, has a wind-driven blade principle where the blades are normally used 3 pieces or 4 blades, but in this design use 3 blades with blade diameter D = 40 mm with radio circular anemometer 180 mm. by arduino and converted through calculations that have been set on the computer using the arduin software. By conducting testing it is expected that the designed anemometer has the same wind speed (Va) value in calculating wind speed. testing by comparing the results of the standard deviation (?) of the product anemometer or design, and also the comparison of values from the results of wind speed (Va) which is tested in the laboratory of the basic phenomena of mechanical engineering with a range of wind speeds tested around 1 m / s to 10 m / s. the standard deviation (?) is obtained for the product anemometer of 3.478% and the design anemometer of 11.07% and the design anemometer has an error data on the product anemometer of 0.4%.